Using training to promote civil service reform: a Tanzanian local government case study - Mccourt, Willy; Sola, Nazar (1999)
Since 1993, Tanzania has been pursuing a programme of civil service reform which has emphasized job reduction. In local government the importance of reform and the lack of previous training for the manpower management officers (MMOs) responsible for job reduction are an argument for training, while the complex institutional arrangements of local government and the difficult circumstances in which the MMOs work are a potential constraint on its effectiveness. A programme of training for the MMOs and its theoretical under-pinnings in terms of transfer of learning are outlined. Discussion of the programme's effectiveness leads to a discussion of the limited effectiveness of even well-designed training in isolation, and of the complementary organizational and institutional development interventions which are desirable in order to increase its effectiveness. - Reproduced
Keywords: Training - Tanzania; Case studies; Local government - Tanzania; Civil service reform - Tanzania; Civil service - Tanzania; Local government